Trends in the Immunomodulatory Effects of Cordyceps militaris: Total Extracts, Polysaccharides and Cordycepin - Lee, Chun-Ting; Huang, Keng-Shiang; Shaw, Jei-Fu; Chen, Jung-Ren; Kuo, Wen-Shuo; Shen, Gangxu; Grumezescu, Alexandru Mihai; Holban, Alina Maria; Wang, Yi-Ting; Wang, Jun-Sheng; Hsiang, Yi-Ping; Lin, Yu-Mei; et al. (Frontiers in Pharmacology, 2020)
Cordyceps militaris (C. militaris) is a fungus with a long history of widespread use in folk medicine, and its biological and medicinal functions are well studied. A crucial pharmacological effect of C. militaris is immunomodulation. In this review, we catalog the immunomodulatory effects of different extracts of C. militaris, namely total extracts, polysaccharides and cordycepin. Total extracts obtained using water or 50% ethyl alcohol and polysaccharides from C. militaris were discovered to tend to promote type 1 immunity, whereas total extracts obtained using 70%–80% ethyl alcohol and cordycepin from C. militaris were more likely to promote type 2 immunity. This article is the first to classify the immunomodulatory effects of different extracts of C. militaris. In addition, we discovered a relationship between different segments or extracts and differing types of immunity. This review can provide the readers a comprehensive understanding on the immunomodulatory effects of the precious folk medicine and guidance on its use for both health people and those with an immuo deficiency.